EVALUASI FUNGSI EKOLOGIS VERTIKAL HIJAU PADA BANGUNAN RUMAH DI KABUPATEN KUPANG NTT - Roosna Maryani O Adjam; Micha Ratu Rihi (Partner, 2018)
Using of green vertical in Indonesia began to develop since 2000. This has been supported by public awareness to create a better quality living space. The vertical greening system in the landscape world has become a common practice for growing vines on building walls. Evaluation study of green vertical ecological functions was carried out in one of the residential houses in Kupang Regency. The basic objective of research is vertical green is needed to replace the function of air conditioner (AC) in homes in creating thermal comfort. The method in this study is the experimental method, carried out by testing several parameters on green vertical. The research procedure consists of 4 main stages, (1) the design and construction of the proposed green vertical model; (2) distance placement arrangements between panels and buildings; (3) selection of plants to be used and (4) measurement of microclimate. The measurement results are then analyzed to compile the green vertical criteria in residentialbuildings. Observation of the study was conducted in July 2018. Based on the laying distance, the best vertical green distance to the building wall was 0 cm (attached to the wall). With a distance of 0 cm, the decrease in room temperature is at the maximum level of 0.68 ° C for indoor conditions and0.86 ° C outside space. While based on the type of plant, the best combination of ground cover in reducing temperature was Marantha leuconeura. Referring to the measurement results, the best combination of panels to be applied on a residential scale was Marantha leuconeura which was placed at a distance of 0 cm from the wall of the building.